Brucella spp. Lumazine synthase as a novel immunomodulator to produce egg yolk antibodies - Bellido, Demian; Chacana, Pablo; Mozgovoj, Marina Valeria; Gonzalez, Diego; Goldbaum, Fernando Alberto; Wigdorovitz, Andres; Dus Santos, Maria Jose (Scientific Research, 2019)
Lumazine synthase from Brucella spp. (BLS) is a highly immunogenic decameric protein. It has been previously described as a carrier of peptides or proteins to increase their immunogenicity in different animal species, but its activity has never been evaluated in chickens. In this work, the use of BLS to improve the antibody response against bovine rotavirus (BRV) VP8d protein in laying hens was assessed. VP8d is the inner domain of the VP8 spike protein which preserves the sialic acid binding activity and the neutralizing epitopes present in the viral protein. Hens were immunized three times with 2 μg of VP8d alone or fused to BLS. Hens inoculated with BLSVP8d developed higher antibody titers (evaluated by ELISA and viral neutralization test) than hens immunized either with VP8d alone or the mixture of VP8d and BLS. Furthermore, IgY antibodies against BLSVP8d were able to fully protect mice against challenge with virulent BRV in a dose-depent-manner. Overall, these results demonstrate that BLS is a potent immonumodulator that enhances the antibody response in hens, thus increasing the concentration of specific IgY in the egg yolk, one of the main issues to be adressed in order to improve the use of the IgY technology.